FRI0571 MEASUREMENT PERFORMANCE OF REDUCED VERSIONS OF MUSCLE STRENGTH TOOLS IN JUVENILE DERMATOMYOSITIS. (June 2019) - Rosina, Silvia; Varnier, Giulia Camilla; Pistorio, Angela; Consolaro, Alessandro; Pilkington, Clarissa; Maillard, Susan; Civino, Adele; Tsitsami, Elena; Inocencio, Jaime de; Jelusic, Marija; Vojinovic, Jelena; Espada, Graciela; et al.
Abstract : Background: Assessment of muscle strength is a fundamental component of the clinical evaluation of children with juvenile dermatomyositis (JDM). Regular measurement of muscle strength in daily care requires the availability of simple and quick muscle assessment tools. Objectives: To investigate whether reduced versions of the MMT8 and CMAS are equally reliable as the original tools. Methods: The following 4 reduced instruments were devised: 1) MMT4 (score 0-40), including 4 items of MMT8 (neck flexors, deltoid middle, gluteus maximus, and gluteus medius); 2) MMT6 (score 0-60), composed of the same items of MMT4 plus biceps brachii and quadriceps; 3) head lift time of CMAS (0-120 seconds or 0-5 points); 4) sum of CMAS head lift time in points and the 6 sit-ups maneuvers of CMAS (score 0-11). Validation was conducted according to OMERACT filter on 213 patients followed in standard clinical care at 13 international pediatric rheumatology centers and evaluated at baseline and after a median of 5.9 months. Results: All reduced instruments revealed strong correlations (r > 0.7) with muscle activity VAS and total DAS, moderate correlations (r = 0.4-0.7) with physician's global VAS, muscle DAS, skin activity VAS, pain VAS, parent's overall wellbeing VAS, and CK. Correlations with skin DAS and fatigue VAS were low (r < 0.4). Cronbach's alpha was excellent (0.92-0.95) for all reduced tools for which this property could be assessed. SRM was good-to-moderate (0.60-0.91) for all reduced instruments in patients judged as improved by the physician. All reduced tools discriminated strongly between patients classified in different disease activity states by the physician (p < 0.0001), and between patients whose parents were satisfied or not satisfied with their children's disease status (p < 0.0001). Overall, the metrologic performance of the reduced instruments was comparable to that of MMT8 and CMAS. Conclusion: We found that reduced versions of the MMT8 and CMAS have good metrologic properties and perform similarly to the original tools in a population of patients followed in standard clinical care. Our results suggest that these simplified and shortened instruments could serve as surrogate for the complete measures in routine practice, particularly in a busy clinical setting. References: [1] Measures of adult and juvenile dermatomyositis, polimyositis, and inclusion body myositis. Rider LG, Werth VP, Huber AM, Alexanderson H, Rao AP, et al. Arthritis Care Res (Hoboken)2011;63:S118-57. [2] Clinical assessment in juvenile dermatomyositis. Ravelli A, Ruperto N, Trail L, Felici E, Sala E, et al. Autoimmunity2006;39:197-203. Disclosure of Interests: Silvia Rosina: None declared, Giulia Camilla Varnier: None declared, Angela Pistorio: None declared, Alessandro Consolaro Grant/research support from: AbbVie, Pfizer, Clarissa Pilkington: None declared, Susan Maillard: None declared, Adele Civino: None declared, Elena Tsitsami: None declared, Jaime de Inocencio: None declared, Marija Jelusic: None declared, Jelena Vojinovic: None declared, Graciela Espada: None declared, Balahan Makay Speakers bureau: Enzyvant, Novartis, Roche, Abbvie, Maria Katsikas: None declared, Polixeni Pratsidou-Gertsi: None declared, Dragana Lazarevic: None declared, Anand Prahalad Rao: None declared, Nicolino Ruperto Grant/research support from: The Gaslini Hospital, where NR works as full-time public employee, has received contributions (> 10.000 USD each) from the following industries in the last 3 years: BMS, Eli-Lilly, GlaxoSmithKline, F Hoffmann-La Roche, Janssen, Novartis, Pfizer, Sobi. This funding has been reinvested for the research activities of the hospital in a fully independent manner, without any commitment with third parties., Consultant for: Received honoraria for consultancies or speaker bureaus (< 10.000 USD each) from the following pharmaceutical companies in the past 3 years: Ablynx, AbbVie, Astrazeneca-Medimmune, Biogen, Boehringer, Bristol-Myers Squibb, Eli-Lilly, EMD Serono, GlaxoSmithKline, Hoffmann-La Roche, Janssen, Merck, Novartis, Pfizer, R-Pharma, SanofiServier, Sinergie, Sobi and Takeda., Speakers bureau: Received honoraria for consultancies or speaker bureaus (< 10.000 USD each) from the following pharmaceutical companies in the past 3 years: Ablynx, AbbVie, Astrazeneca-Medimmune, Biogen, Boehringer, Bristol-Myers Squibb, Eli-Lilly, EMD Serono, GlaxoSmithKline, Hoffmann-La Roche, Janssen, Merck, Novartis, Pfizer, R-Pharma, SanofiServier, Sinergie, Sobi and Takeda., Angelo Ravelli Grant/research support from: Angelini, AbbVie, Bristol-Myers Squibb, Johnson & Johnson, Novartis, Pfizer, Reckitt Benkiser, and Roche, Consultant for: Angelini, AbbVie, Bristol-Myers Squibb, Johnson & Johnson, Novartis, Pfizer, Reckitt Benkiser, and Roche, Speakers bureau: Angelini, AbbVie, Bristol-Myers Squibb, Johnson & Johnson, Novartis, Pfizer, Reckitt Benkiser, and Roche